Quantum chemical calculation of excited states of flavin-related molecules - Neiß, Christian; Saalfrank, Peter; Parac, Maja; Grimme, Stefan (Journal of Physical Chemistry A, 2003)
The performance of various methods of various quantum mechanical methods for the calculation of low-lying singlet and triplet excited states of biologically relevant species related to flavins is critically examined. In particular, configuration interaction singles (CIS), time-dependent density functional theory (TD-DFT), and the recently proposed multireference configuration interaction DFT method (DFT/MRCI) [Grimme, S.; Waletzke, M. J. Chem. Phys. 1999, 111, 5645] are compared. For the DFT-based methods, various hybrid exchange-correlation functionals are used. For the "test molecule" uracil, it is found that CIS does not give quantitatively accurate energies even in conjunction with large basis sets including diffuse functions. In contrast TD-DFT(B3LYP) and DFT/MRCI produce reasonably accurate results even with medium-sized basis sets such as 6-31G*. Following these test calculations, the absorption energies of the lumiflavin molecule in its ground (i.e., S → S ) and lowest triplet state (i.e., T → T ) are investigated. The nature of the low-lying excited states is discussed, and the results are compared to experiment. Finally, the effect of surrounding water molecules and of geometrical distortions on the absorption spectrum of flavin-type species is discussed on the basis of model calculation